Perceptual synergy between seeing and hearing revealed during binocular rivalry - Kang, Min-Suk; Blake, Randolph (Psichologija, 2005)
When the two eyes view dissimilar images, the observer experiences alternations in perceptual dominance between the two stimuli, with the individual durations of dominance varying randomly throughout a prolonged sequence of alternations. In this study, we paired an amplitude-modulated sound with a flickering rival grating and found that the sound had a small but statistically reliable influence on the durations of dominance of the flickering grating: those durations were longer, on average, when the flickering grating and the sound were coincident. An effect of sound was not observed during suppression phases of the flickering grating, nor was it found when the tone was steady. This bisensory interaction represents yet another example of neural interactions between vision and audition.